PUPPET KHANS» OF THE CHIGATAY ULUS AND THEIR ACTIVITIES IN MUSLIM SOURCES - Sevinch Ulashova (Web of Journals Publishing, 2025)
This article analyzes the phenomenon of «puppet khans» formed during the decline of the Chigatay ulus in Muslim historical sources and their political and administrative activities. The study, especially in the 14th-15th centuries in the Western Chigatay ulus - in particular, in Maveraunnahr – sheds light on the historical processes related to the weakening of the central government in the 14th-15th centuries, when the khans were deprived of real political power and in fact the Turkic emirs and other military-aristocratic groups took power. In the works of historians such as Nizamiddin Shami, Sharafuddin Ali Yazdi, Muiniddin Natanzi, Khandamir, Mirzo Haydar, these khans are mentioned as a symbol of power and legitimacy, but their independent political activities are clearly limited. The article is aimed at re-evaluating the processes of disintegration of the Chigatay ulus, the policy pursued through «puppet khans», and their place in the historical and cultural heritage.
Keywords: Chigatay ulus, puppet khans, Muslim sources, Timurids, Maveraunnahr, political history.